A Multisite Evaluation of Prosecutor-Led Pretrial Diversion: Effects on Conviction, Incarceration, and Recidivism. (October 2021) - Davis, Robert C.; Reich, Warren A.; Rempel, Michael; Labriola, Melissa
Recent years have witnessed a resurgence of interest in prosecutor-led pretrial diversion programs, yet up-to-date research on the effectiveness of these programs is lacking. Participants in four prosecutor-led diversion programs, Cook County, IL (separate analyses for misdemeanor and felony participants), Milwaukee County, WI (two distinct programs varying in participant risk level and treatment intensity), and Chittenden County, VT, were propensity-score matched to comparison defendants (total n = 5, 040). All programs yielded a significant decrease in instant case conviction (mean odds ratio = .12) and use of jail sentences (mean odds ratio = .33). There was also a trend toward reduced re-arrest at 2 years (mean odds ratio = .79). Three of four diversion programs significantly delayed onset of first re-arrest. Taken together, results support the effectiveness of a diverse set of prosecutor-led pretrial diversion programs that varied in charge severity, participant risk level, and program duration and intensity.